Augusto Graziani and general economic equilibrium: from statics to dynamics. (September 2016) - Pomini, Mario
Abstract : Graziani has always maintained an attitude of great respect and admiration for the theory of general equilibrium. In his 1965 book, he managed to solve the problematic elements contained in the static part of the theory. Abandoning the original assumptions and introducing new specifications, he tried to demonstrate the logical consistency of all systems of equations. The real issue was posed by the dynamic part of the theory. Economic dynamics is a process of structural change and not the quiet path of some sort of steady-state process. The attempt proposed by Graziani in the 1960s to turn the static general equilibrium into a dynamic one produced an interesting result. Graziani's dynamic approach in many respects has the same logical structure as the endogenous growth literature that flourished in the 1980s and 1990s. Graziani's contribution is relevant not only from the point of view of the historical analysis of the evolution of economic ideas, but, most importantly, it can contribute to clarifying the roots of the new approach to economic growth.